The role of water on the electronic transport in graphene nanogap devices designed for DNA sequencing. (March 2020) - de Freitas Martins, Ernane; Amorim, Rodrigo G.; Feliciano, Gustavo Troiano; Scheicher, Ralph Hendrik; Rocha, Alexandre Reily
Abstract: Innovative methodologies for reliably and inexpensively sequencing DNA can lead to a new era of personalized medicine. In this work, we performed a theoretical investigation of a nanogap-based all electronic DNA sequencing device. To do so, we used a nitrogen-terminated nanogap on a graphene sheet with the aqueous environment fully taken into account. Our investigation is performed using a hybrid methodology combining quantum and classical mechanics coupled to non-equilibrium Green's functions for solving the electron transport across the device. The obtained results show that the DNA nucleotides can be both detected and distinguished in such a device, which indicates that it can be used as a DNA sequencing device providing very high sensitivity and selectivity. Furthermore, our results show that water plays a major role in electronic transport in nanoscopic tunneling devices, not only from an electrostatics point of view, but also by providing states that significantly increase the conductance in nanogap-based DNA sequencing devices. Graphical abstract: Image 1